Rancang Bangun Prototype Sistem Keamanan Rumah Dan Monitoring Peralatan Listrik Dengan Sms Gateway Dan Validasi Telepon - Fiqi Arfian; Ade Zulkarnain Hasibuan; sayuti rahman (SNASTIKOM, 2022)
Advanced technology has many benefits for its users. One way to protect the home by utilizing home securitysystem technology. Fire and theft are major problems that must be considered in home security. Several factorsfor the occurrence of fires and theft in the house are due to the negligence of the owner of the house itself and thedelay in handling and prevention. Incidents like this can result in material losses and even fatalities. Therefore,the purpose of this research is to create a tool that can monitor security and home electrical equipment at anytime by using Arduino as a medium of information that will be sent via short SMS messages and phone calls. Thisdevice can also control home electrical appliances remotely automatically with SMS commands. The test resultsshow that this system can provide accurate information to homeowners and can monitor security and homeelectrical equipment.